Computational methodology and molecular dynamics analysis of andrographolide bioactivity against Cutibacterium acnes - Lin, Min; He, Lihui; Ye, Guodong; Zhao, Xiaotian (Frontiers in Chemistry, 2025)
Cutibacterium acnes (formerly known as Propionibacterium acnes) is a Gram-positive anaerobic bacterium that is frequently found in sebaceous glands and human skin hair follicles. Although it is a normal component of the skin microbiota, acne may result from its overgrowth in specific situations. Andrographis paniculate, a traditional Chinese herb, contains a diterpenoid compound called andrographolide (AGP), which has anti-inflammatory, antibacterial and antioxidant. AGP can strengthen the skin barrier functions by preventing the release of inflammatory factors like TNF-α and IL-6. It has also shown that its antibacterial qualities can inhibit pathogens such as Cutibacterium acnes. In this study, through the use of the quantum chemistry approach, we investigated AGP in DMSO and gas phase, in connection to the geometric foundations and energy dynamics by Density Functional Theory (DFT). Furthermore, this work has been carried out on the structural analysis by orbital examination and electrostatic potential (ESP) assessment. Subsequently, we derived the molecular interactions utilizing the independent gradient model within Hirshfeld molecular density partitioning (IGMH). Additionally, the stability and interaction of AGP and fusidic acid with the protein CAlipase of Cutibacterium acnes have been investigated by molecular docking and molecular dynamics simulations. This study might provide a fresh perspective for investigating an effective extraction process via methodological analytical discussions.